The Relationship Between Motivation and Job Satisfaction in Gen Z - Chaeriah, Nurul (Journal of Business Inflation Management and Accounting, 2025)
Generation Z started to enter the workplace as they are on their prime era. As generation who raised in the glamor of technology and liberalism, Generation Z have a different perspective about life, including work-related stuff. This study aims to investigate Generation Z's distinct working preferences while examining the complex relationship between motivation and job satisfaction. By reviewing several academics paper, it’s conclude that opportunities for personal growth and meaningful work are two examples of intrinsic motivation that are crucial for promoting job satisfaction in Gen Z. These intrinsic motivations are further influenced by extrinsic factors such as job stability, managerial support, and financial incentives, which together provide a balanced framework. Future studies should put some attention into generational preferences across different industries and the long-term impacts of global disruptions like the COVID-19 pandemic. Organizations are recommended to customize incentive techniques to include flexibility, acknowledgment, and equitable treatment. These observations offer a strong basis for raising Gen Z's level of job satisfaction and organizational engagement.